Stanford video guide to negotiating the sluggers come home - Neal, Margaret
"A negotiation between the owners of a baseball stadium and a team owner demonstrates key principles of rational negotiation and common tactics and strategies for negotiating profitable agreements." In three parts: Preparation, Bargaining and Settlement.